Intracellular Delivery by Shape Anisotropic Magnetic Particle–Induced Cell Membrane Cuts. (August 2016) - Lin, Ming-Yu; Wu, Yi-Chien; Lee, Ji-Ann; Tung, Kuan-Wen; Zhou, Jessica; Teitell, Michael A.; Yeh, J. Andrew; Chiou, Pei Yu
Introducing functional macromolecules into a variety of living cells is challenging but important for biology research and cell-based therapies. We report a novel cell delivery platform based on rotating shape anisotropic magnetic particles (SAMPs), which make very small cuts on cell membranes for macromolecule delivery with high efficiency and high survivability. SAMP delivery is performed by placing commercially available nickel powder onto cells grown in standard cell culture dishes. Application of a uniform magnetic field causes the magnetic particles to rotate because of mechanical torques induced by shape anisotropic magnetization. Cells touching these rotating particles are nicked, which generates transient membrane pores that enable the delivery of macromolecules into the cytosol of cells. Calcein dye, 3 and 40 kDa dextran polymers, a green fluorescence protein (GFP) plasmid, siRNA, and an enzyme (β-lactamase) were successfully delivered into HeLa cells, primary normal human dermal fibroblasts (NHDFs), and mouse cortical neurons that can be difficult to transfect. The SAMP approach offers several advantages, including easy implementation, low cost, high throughput, and efficient delivery of a broad range of macromolecules. Collectively, SAMP delivery has great potential for a broad range of academic and industrial applications.